2013
DOI: 10.1080/03235408.2013.792536
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of neem compost on root knot nematode pest of Lagos spinach,Celosia argentea

Abstract: The effects of neem compost on root knot nematode, Meloidogyne incognita, pest of Lagos spinach, Celosia argentea, cv. TLV 8, was studied during 2010 and 2011 planting seasons on the field. The trial was conducted at the Teaching and Research Farm of Ladoke Akintola University of Technology, Ogbomoso, Nigeria. There were four treatments, replicated five times fitted into randomised complete block design. Neem compost was applied at 1.0, 1.5 and 2.0 tonnes/ha. Experimental plots, where no compost was applied se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
2
4
0
Order By: Relevance
“…The results of this experiment corroborate with those of Yakubu and Izuogu, (2013) on the evaluation of botanicals on root-knot nematodes where such active ingredients were found to suppress nematode populations in the field. Olabiyi et al, (2013) also reported similar findings of the efficacy of neem compost on nematodes in spinach. Several other plants and organic materials have also been reported to contain different metabolites necessary for plant growth, better yield and at same time toxic to pathogenic microorganisms in the soil.…”
Section: Meloidogynesupporting
confidence: 64%
See 1 more Smart Citation
“…The results of this experiment corroborate with those of Yakubu and Izuogu, (2013) on the evaluation of botanicals on root-knot nematodes where such active ingredients were found to suppress nematode populations in the field. Olabiyi et al, (2013) also reported similar findings of the efficacy of neem compost on nematodes in spinach. Several other plants and organic materials have also been reported to contain different metabolites necessary for plant growth, better yield and at same time toxic to pathogenic microorganisms in the soil.…”
Section: Meloidogynesupporting
confidence: 64%
“…There is increasing need to find more acceptable alternatives. The potential for nematicidal activity of indigenous plants and their products has been reported by earlier workers (Adekunle and Fawole, 2003;., 2009, 2010, 2011, 2012Yakubu and 2013;Olabiyi et al, 2013). The nematicidal principles of plant origin in the form of isothiocyanates, thiophenics, glucosides, alkaloids, phenolics, thianins and fatty acids have been identified (Fatoki and Fawole, 2000).…”
Section: Introductionmentioning
confidence: 62%
“…They pointed out that active ingredients contained in the plant materials suppressed the nematode populations in the field. Olabiyi et al [25] Also reported similar findings of the efficacy of neem compost on nematodes in spinach. Several plants and organic materials have also been reported to contain different metabolites necessary for plant growth, better yield and at same time toxic to pathogenic microorganisms in the soil [26].…”
Section: Discussionmentioning
confidence: 64%
“…Freshly harvested Siam weed was shredded into smaller pieces. 100 kg of chopped leaves was mixed thoroughly with 15 kg of poultry manure gotten from deep litter poultry house and wrapped with plastic, properly covered for a period of six month prior to the beginning of the research workwindrone method (Olabiyi et al 2013). The mixture was properly turned at an interval of one month with garden spade.…”
Section: Preparation Of Compost Materialsmentioning
confidence: 99%
“…The mixture was properly turned at an interval of one month with garden spade. The fully decomposed materials (compost) were spread, air dried and ground into powder form (Olabiyi et al 2013). Field experiment A field trail was conducted in a plot naturally infested with M. incognita in the year 2017 and repeated at the same period in the 2018 at the site located in the experimental field of 267.3 m 2 (15.5 × 22.8 m).…”
Section: Preparation Of Compost Materialsmentioning
confidence: 99%